Carved Ceiling of the Garbhagriha of the Shiva Temple (Temple 1) - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) of the Shiva Temple (Temple 1) in Cluster 1 is a plain square chamber with a carved ceiling. The ceiling shows a full-blown flower with layered petals enclosed within a square frame.